Uma atividade experimental para o estudo de funções no ensino fundamental - Prospero, Matheus de Barros Ramos (2013)
Functions represent a very important area of study in mathematics due their wide range of applications in many areas of knowledge. Functions can be approached in concrete and meaningful ways. However, school textbooks often tend to an algebraization of the theme, which hinders students' understanding of the need and importance of studying functions. This work does not focus on formal definitions involved in the teaching of functions. The aim of this work is to present an experiment which allows the development of the concept of functions. The experiment is based on a proposed problem of building a box without a lid using a rectangular sheet of paper, and then calculating its volume. This experiment was carried out in two 8th year classes of a public school in Ribeirao Preto - SP, Brazil. The procedure was carried out successfully and students enjoyed it. This is a low-cost, practical project, feasible to any teacher willing to approach the theme in a practical way.